Volitional personality trait change can people choose to change their personality traits? [article]. - Hudson, Nathan W.; Fraley, R. Chris
Previous research has found that most people want to change their personality traits. But can people actually change their personalities just because they want to? To answer this question, we conducted 2, 16-week intensive longitudinal randomized experiments. Across both studies, people who expressed goals to increase with respect to any Big Five personality trait at Time 1 tended to experience actual increases in their self-reports of that trait-as well as trait-relevant daily behavior-over the subsequent 16 weeks. Furthermore, we tested 2 randomized interventions designed to help participants attain desired trait changes. Although 1 of the interventions was inefficacious, a second intervention that trained participants to generate implementation intentions catalyzed their ability to attain trait changes. We also tested several theoretical processes through which volitional changes might occur. These studies suggest that people may be able to change their self-reported personality traits through volitional means, and represent a first step toward understanding the processes that enable people to do so. -- (from the authors)